Influence of Maternal Diet on Flavor Transfer to Amniotic Fluid and Breast Milk and Children's Responses: A Systematic Review (P11-029-19). (13th June 2019) - Spahn, Joanne; Callahan, Emily; Spill, Maureen; Wong, Yat Ping; Benjamin-Neelon, Sara; Birch, Leann; Black, Maureen; Briefel, Ronette; Cook, John; Faith, Myles; Mennella, Julie; Casavale, Kellie
Abstract: Objectives: Systematic reviews were completed to examine the relationships between maternal diet during pregnancy and lactation; amniotic fluid flavor; breast milk flavor, and children's food acceptability and overall dietary intake into adulthood. Methods: A literature search was conducted in 10 databases (e.g., Pubmed, Embase, Cochrane, and CINAHL) to identify articles published from January 1980 to June 2017. Data from each included study were extracted, risk of bias assessed, evidence synthesized qualitatively, conclusion statements developed, and strength of the evidence graded. Results: Twenty-five articles met a priori criteria; 11 articles were relevant for the relationship between maternal diet, amniotic fluid flavor, and infant flavor acceptance and dietary intake; 15 articles were relevant for the relationship between maternal diet, breast milk flavor, and infant flavor acceptance and dietary intake. One article was included in both reviews. Limited but consistent evidence indicates that flavors (alcohol, anise carrot, garlic) originating from the maternal diet during pregnancy can transfer to and flavor amniotic fluid, and fetal flavor exposure increases acceptance of the exposed flavor during infancy and potentially childhood. Moderate evidence indicates that flavors originating from the maternal diet during lactation (alcohol, anise, caraway, carrot, eucalyptus, garlic, mint) transmit to and flavor breast milk in a time-dependent manner. Moderate evidence indicates that infants can detect flavors from the maternal diet through breast milk. This occurs within hours (alcohol, garlic, vanilla), within days (garlic, carrot juice), and within months (cereal flavored with a variety of vegetables including carrot) following maternal ingestion of those flavors during lactation. Findings may not generalize to all foods and beverages. Conclusions cannot be drawn regarding the relationship between mothers' diet during either pregnancy or lactation and overall dietary intake of infants or children. Conclusions: Maternal diet during pregnancy and lactation may provide the earliest opportunity to influence child food acceptance. Funding Sources: USDA Food and Nutrition Service, Alexandria, VA.